Prevalensi insomnia pada mahasiswa fakultas kedokteran universitas Udayana - Dasheni Sathivel; Lely Setyawati (DiscoverSys Inc., 2017)
Background: Insomnia is a sleep disorder that is very common among the people, especially students at this time. A common cause of insomnia is stress, anxiety, medical conditions, medications and others. Insomnia can be classified in several ways, based on the symptoms (difficulty staying asleep, difficulty sleeping, non-restorative sleep), duration (acute, chronic and transient) and based on the cause (primary, secondary). Symptoms of insomnia are less attentive, daytime sleepiness, daytime fatigue, anxiety and more. Insomnia already brought a lot of impact on our lives. If someone continues from suffering this problem, they will face many complications such as poor performance at work or school, irritability, psychiatric problems and more. This study aims to find out about the occurrence of insomnia among students of the Faculty of Medicine, University of Udayana. Methods: this study used descriptive method. Samples have been selected from the 50 semester students 1. Data were collected using a questionnaire. Results: From the results obtained, 20 (40%) of respondents have a sub-threshold insomnia, 28 (56%) of respondents suffer from insomnia clinical severity of moderate and 2 (4%) of respondents suffer from clinically severe insomnia. Conclusions: The majority of medical students suffer from insomnia.